Beyond the Ledger: A Conceptual Review of Social Accounting and Gender Equality and Social Inclusion (GESI) Practices in Library Financial Management - Eogenie Lakilaki; Muhamad Zaky Ramadhan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Public libraries are increasingly recognised as social institutions that promote equity, inclusion, and community wellbeing. However, the integration of Gender Equality and Social Inclusion (GESI) principles into library budgeting remains underexplored. This study employs a narrative literature review to examine how GESI considerations are incorporated into library financial management through the lenses of Social Accounting Theory and Public Value Theory. The findings reveal that library budgeting continues to be dominated by efficiency oriented approaches, often overlooking distributive justice and social equity objectives. The review identifies accessibility oriented budgeting and community empowerment budgeting as the primary forms of inclusive resource allocation while highlighting persistent tensions between managerial efficiency and equity goals. Furthermore, a gap exists between institutional commitments to inclusion and actual budgetary support. To address this issue, the study proposes a GESI Integrated Social Budgeting Framework comprising equity based needs assessment, inclusive budget formulation, participatory allocation, social impact measurement, and accountability reporting. The framework positions budgeting as a strategic instrument for advancing social inclusion and public value creation